Enhanced Decision Making through Probabilistic Shipwreck Risk Assessment: Focusing on the Situation in Greece - Ventikos, Nikolaos P.; Louzis, Konstantinos; Koimtzoglou, Alexandros; Delikanidis, Pantelis (Frontiers in Marine Science, 2016)
The potential leakage of oil trapped in the hull of fully or partially submerged shipwrecks has been a growing concern worldwide mainly due to major uncertainties therein and the great potential for environmental damage. The high cost of either preventing or reacting to potential oil discharges from shipwrecks into the environment mandates the use of risk analysis methods in order to identify the most dangerous cases and prioritize the allocation of resources. The purpose of this study is to present a probabilistic risk assessment method that will incorporate the various uncertainties into a structured and quantitative approach. One of the main factors affecting the release of oil from a shipwreck is the amount and progression of corrosion of the steel structure of the wreck, which is a dynamic process. The proposed model will take this into account by applying a time dependent approach that can be used to forecast how the risk rating, that is calculated for each case, changes as a function of time. The analysis will be concluded by applying a sensitivity analysis for the calibration of the model results. Geographically, this study will focus on Greece which presents a particularly interesting case due to its unique geomorphology and its rather developed maritime domain that is a direct consequence thereof. The great number of islands situated in Greece present an additional concern from a risk perspective because oil spill response operations are therefore constituted extremely difficult and costly. Another consideration, which is directly related to the high value of the various tourist activities, is the fact that even a small amount of spilled oil could be catastrophic for the local economies if the response is not fast enough. These issues indicate a growing need for the application of risk analysis tools that will aid in the decision making process relating to the optimum allocation of resources that are needed to efficiently address the problem as well as the prioritization of the most environmentally dangerous shipwrecks.